The Impact of CEO Succession with Gender Change on Firm Performance and Successor Early Departure: Evidence from China’s Publicly Listed Companies in 1997–2010 - Zhang, Yan; Qu, Hongyan (Academy of Management Journal, 2016)
Female corporate leadership has drawn increasing attention from academia and practitioners. We contribute to the literature by examining the impact of CEO succession with gender change—i.e., a male CEO succeeded by a female or vice versa. We propose that due to gender differences in executive leadership positions, CEO succession with gender change may amplify the disruption of the CEO succession process and thus adversely affect post-succession firm performance and increase the likelihood of successor early departure. Using data from 3,320 CEO successions in companies listed in China’s Shanghai and Shenzhen Stock Exchanges from 1997 to 2010, we find evidence to support this argument. We also find that the negative (positive) impact of male-to-female succession on firm performance (the likelihood of successor early departure) may be weakened by positive organizational attitudes toward female leadership as indicated by the presence of other female leaders on the firm’s board of directors and/or top management team, and the successor’s inside origin.